School breakfast and body mass index: a longitudinal observational study of middle school students. Issue 3 (17th March 2016) - Wang, S.; Schwartz, M. B.; Shebl, F. M.; Read, M.; Henderson, K. E.; Ickovics, J. R.
Summary: Objectives: The objectives are to identify breakfast location patterns (frequency and place of breakfast consumption) and explore the association between breakfast patterns and weight status over time among preadolescents. Methods: Surveys and physical measurements were completed among students from 12 randomly selected schools in a medium‐sized urban school district. All students were followed from fifth (Fall, 2011) to seventh grade (Fall, 2013). Latent transition analysis and longitudinal analyses were used in the study. Results: Six distinct breakfast location patterns emerged at baseline (1) frequent skippers; (2) inconsistent school eaters; (3) inconsistent home eaters; (4) regular home eaters; (5) regular school eaters and (6) double breakfast eaters. Results from the longitudinal analyses revealed that there was an increased odds of overweight/obesity among frequent skippers compared with double breakfast eaters after adjusting for school, year and students' race/ethnicity (AOR: 2.66, 95% CI: 1.67, 4.24). Weight changes from year to year were similar between double breakfast eaters and other students. Conclusions: Concerns that a second breakfast at school increases risk of excessive weight gain are unsupported. Students who regularly consumed breakfasts at school, including double breakfast eaters, were more likely to exhibit a healthy weight trajectory. Additional research is needed to understand the impact of universal school breakfast on students' overall diets.